The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14237269
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Role of Nanometric Molybdenum–Vanadium Carbides in Mitigating Hydrogen Embrittlement in Structural Steels

Abstract: The influence of hydrogen on the fracture toughness and fatigue crack propagation rate of two structural steel grades, with and without vanadium, was evaluated by means of tests performed on thermally precharged samples in a hydrogen reactor at 195 bar and 450 °C for 21 h. The degradation of the mechanical properties was directly correlated with the interaction between hydrogen atoms and the steel microstructure. A LECO DH603 hydrogen analyzer was used to study the activation energies of the different microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
0
6
1
Order By: Relevance
“…The high HE susceptibility of the cast variant was attributed to the platelet structure of pearlite and H trapping at carbides, leading to increased H concentration. This observation seemingly contrasts with other research indicating a protective role of carbides as strong traps mitigating HE, as suggested by other authors. , …”
Section: Knowledge Base About Hecontrasting
confidence: 99%
See 1 more Smart Citation
“…The high HE susceptibility of the cast variant was attributed to the platelet structure of pearlite and H trapping at carbides, leading to increased H concentration. This observation seemingly contrasts with other research indicating a protective role of carbides as strong traps mitigating HE, as suggested by other authors. , …”
Section: Knowledge Base About Hecontrasting
confidence: 99%
“…This observation seemingly contrasts with other research indicating a protective role of carbides as strong traps mitigating HE, as suggested by other authors. 570,571 The 17−4 precipitation-hardened stainless steel fabricated via L-PBF exhibits a microstructural divergence from its conventionally produced counterpart, too. Typically, wrought 17−4 precipitation-hardened stainless steel has a martensitic microstructure.…”
Section: Bcc Iron and Steelsmentioning
confidence: 99%
“…The mean value can be even higher than that of the interstitial sites. Adding deep traps such as interfaces between carbides and the metal can bind internal hydrogen and protect the metal from hydrogen embrittlement [34][35][36][37] -as long as there is no external hydrogen source.…”
Section: Microstructural Contributions To Solubilities In the Low Con...mentioning
confidence: 99%
“…Hydrogen is generally considered a kind of point defect in metals and alloys, which can interact with other defects and significantly reduce the ductility of materials even when the H content is quite low. This phenomenon is known as hydrogen embrittlement (HE) [ 1 , 2 , 3 , 4 ]. The detrimental effect of H is a long-standing problem for structural materials.…”
Section: Introductionmentioning
confidence: 99%